2023
DOI: 10.1039/d2ay02031a
|View full text |Cite
|
Sign up to set email alerts
|

Green and rapid synthesis of biomass carbon dot-based fluorescence sensing for the sensitive determination of oxytetracycline

Abstract: An eco-friendly biomass carbon dots (CDs) with blue fluorescence emission was rapidly synthesized by microwave method. Based on the inner filter effect (IFE) between oxytetracycline (OTC) and CDs, the fluorescence...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 29 publications
0
2
0
Order By: Relevance
“…An energy efficient and low timeconsuming MW-assisted method has also been explored with chemical and biomass precursors to derive functional CDs. 76,77 Li et al 78 applied MW treatment (3 min) to a mixture of carbonized laver (biomass) and PEG to yield blue-emitting CDs for the detection of oxytetracycline. In another recent report, citric acid (CA) and tris base were used as starting precursors to synthesize CDs via the MW method.…”
Section: Bottom-up Approachmentioning
confidence: 99%
“…An energy efficient and low timeconsuming MW-assisted method has also been explored with chemical and biomass precursors to derive functional CDs. 76,77 Li et al 78 applied MW treatment (3 min) to a mixture of carbonized laver (biomass) and PEG to yield blue-emitting CDs for the detection of oxytetracycline. In another recent report, citric acid (CA) and tris base were used as starting precursors to synthesize CDs via the MW method.…”
Section: Bottom-up Approachmentioning
confidence: 99%
“…In recent years, natural substances have gradually become ideal carbon sources for CDs owing to their advantages of abundant derivation, easy collection, environmental protection, and low depletion [26]. At present, plenty of studies have been reported on the preparation of CDs by utilizing natural materials such as bee pollen [27], banana stems [28], and laver [29] as carbon sources.…”
mentioning
confidence: 99%